Mind the blind spot: The experience of fathering for men who are violent to their partners - Heward-Belle, Susan (2014)
This thesis explored the fathering of 17 men who had been violent to their female partners. This subject remains largely unexamined despite evidence documenting the harmful impacts of domestic violence on children and young people. Conversely, women’s mothering continues to be intensely scrutinized, particularly by child protective services. By focusing on fathering, this inquiry challenges socially unjust approaches, which hold survivors, rather than perpetrators accountable for the harmful impacts of domestic violence. The following research questions guided the inquiry: What are men’s perceptions regarding the nature, extent and severity of domestic violence in their families? How do they describe the impact of their violence on women and children? How do they describe their fathering experiences and practices? How do they describe their relationships with their children? These questions were explored utilizing an approach, which integrated critical feminist understandings of domestic violence, drawing upon radical, poststructural and intersectional perspectives. A primarily qualitative method using a purposive sample and semi-structured, in-depth interviews was utilised. The analysis showed that men’s fathering was varied. Variations were particularly evident when comparisons were made between men’s identification with hegemonic masculinity and men’s beliefs about control over violence and other coercive behaviours. Men used their privileged positions as fathers to oppress women and children. Harmful fathering practices and exposure to domestic violence placed children and young people at risk in various ways. The intersection of constructions of masculinity with other aspects of men’s identities, particular their class, culture and health contributed to the diversity of harmful fathering practices. The findings underscore the need to develop strategies that hold men accountable for their violence and harmful fathering practices. The possibilities for developing social work interventions targeting men, which are based upon intersectional approaches are discussed as a way forward in future efforts to address men’s violence against women and children